Implementasi Perda Kabupaten Sukabumi Nomor 7 Tahun 2024 di Kampung Adat Ciptarasa - Burman, Naswa Syakila Amalia; Kusumah, Haidan Angga (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the implementation of legal protection of the constitutional rights of customary law communities (MHA) based on Sukabumi Regency Regional Regulation Number 7 of 2024 which applies in the Ciptarasa Traditional Village. Although recognition of MHA has been affirmed in Article 18B paragraph (2) of the 1945 Constitution, in reality, many indigenous communities still face gaps in obtaining administrative recognition, access to public services, and participation in the policy-making process. The purpose of this study is to examine the extent to which the regional regulation is able to provide effective and fair legal protection to indigenous peoples, as well as identify inhibiting factors and solutions that can be offered. The research method used is empirical juridical, with a qualitative approach. Data was obtained through document studies, interviews, and field observations in Ciptarasa Village. The analysis was conducted based on the theory of legal protection from Philipus M. Hadjon and the theory of social justice from John Rawls. The results of the study show that although the regional regulation has provided formal recognition of the existence of Kampung Ciptarasa as an indigenous community, substantive protection of their rights has not been fully realized. The main obstacles include the lack of socialization of regional regulations, limited population administration services, lack of budget, and weak participation of indigenous peoples in policy formulation. Therefore, it is necessary to strengthen the role of customary institutions, integrate community-based public services, as well as budget commitments and periodic evaluations so that this regional regulation is not only symbolic, but truly guarantees the constitutional rights of customary law communities in real terms.